Coupled Mo-U abundances and isotopes in a small marine euxinic basin: Constraints on processes in euxinic basins. (1st February 2018) - Bura-Nakić, Elvira; Andersen, Morten B.; Archer, Corey; de Souza, Gregory F.; Marguš, Marija; Vance, Derek
Abstract: Sedimentary molybdenum (Mo) and uranium (U) abundances, as well as their isotope systematics, are used to reconstruct the evolution of the oxygenation state of the surface Earth from the geological record. Their utility in this endeavour must be underpinned by a thorough understanding of their behaviour in modern settings. In this study, Mo-U concentrations and their isotope compositions were measured in the water column, sinking particles, sediments and pore waters of the marine euxinic Lake Rogoznica (Adriatic Sea, Croatia) over a two year period, with the aim of shedding light on the specific processes that control Mo-U accumulation and isotope fractionations in anoxic sediment. Lake Rogoznica is a 15 m deep stratified sea-lake that is anoxic and euxinic at depth. The deep euxinic part of the lake generally shows Mo depletions consistent with near-quantitative Mo removal and uptake into sediments, with Mo isotope compositions close to the oceanic composition. The data also, however, show evidence for periodic additions of isotopically light Mo to the lake waters, possibly released from authigenic precipitates formed in the upper oxic layer and subsequently processed through the euxinic layer. The data also show evidence for a small isotopic offset (∼0.3‰ on 98 Mo/ 95 Mo) between particulate and dissolved Mo, even at highest sulfide concentrations, suggesting minor Mo isotope fractionation during uptake into euxinic sediments. Uranium concentrations decrease towards the bottom of the lake, where it also becomes isotopically lighter. The U systematics in the lake show clear evidence for a dominant U removal mechanism via diffusion into, and precipitation in, euxinic sediments, though the diffusion profile is mixed away under conditions of increased density stratification between an upper oxic and lower anoxic layer. The U diffusion-driven precipitation is best described with an effective 238 U/ 235 U fractionation of +0.6‰, in line with other studied euxinic basins. Combining the Mo and U systematics in Lake Rogoznica and other euxinic basins, it is apparent that the two different uptake mechanisms of U and Mo can lead to spatially and temporally variable Mo/U and Mo-U isotope systematics that depend on the rate of water renewal versus removal to sediment, the sulfide concentration, and the geometry of the basin. This study further emphasises the potential of combining multiple observations, from Mo-U enrichment and isotope systematics, for disentangling the various processes via which redox conditions control the chemistry of modern and ancient sediments.